Challenges of Online Teaching during COVID-19 Pandemic and Lessons Learned - Acharya, Milan; Acharya, Kamal Prasad (Education and Development, 2021)
This study explores the existing ICT competencies of high school teachers in online mode during the COVID-19 pandemic. It also identifies the challenges and opportunities faced by school teachers in teaching and learning. The study followed the mixed method (QUAN-qual) research design. A total of eighteen teachers have been selected purposively at Kirtipur municipality. A set of questionnaires and an in-depth interview guideline were prepared for data collection. The quantitative and qualitative data were analyzed by using the SPSS software version 20 and the verbatim and thematic methods. The obtained quantitative data were interpreted by using statistical tools like correlation and the significance through Spearman's Rho rank-order correlation coefficient bivariate analysis. The result showed that almost all teachers had the basic knowledge of ICT tools and the knowledge for handling them. About 72 percent of them used Zoom and the rest 28 percent of them used other software like Microsoft teams and messenger. The popularity of using the face-to-face lecture method of teaching, problems with internet access and laptops, and inadequate ICT-friendly environment are the major challenges for online teaching and learning.